Reduced Radial Peripapillary Capillary in Pathological Myopia Is Correlated With Visual Acuity - Ye, Jie; Lin, Jue; Shen, Meixiao; Chen, Wen; Zhang, Riyan; Lu, Fan; Shao, Yilei (Frontiers in Neuroscience, 2022)
Purpose To quantify the radial peripapillary capillary (RPC) density and the peripapillary retinal nerve fiber layer (pRNFL) thickness in pathological myopia and examine associations among these factors and best-corrected visual acuity (BCVA). Methods The cohort was composed of 41 eyes as control and 79 eyes with high myopia (59 simple high myopia, 20 pathological myopia). Optical coherence tomography angiography was done to obtain RPC density and pRNFL thickness, superficial retinal capillary plexus (SRCP), and deep retinal capillary plexus (DRCP) density. The axial length (AL) was measured. Correlations among BCVA, RPC density, pRNFL thickness, AL, and other parameters were determined. Results For pathological myopia, the densities of RPC, SRCP, and DRCP were significantly less than those of the control and simple high myopia groups (p ≤ 0.005). There was no statistical difference in pRNFL thickness between pathological myopia and simple high myopia (p = 0.063), whereas there was significant difference in global pRNFL thickness between pathological myopia and control (p = 0.008). The global RPC density showed the greatest area under the curve (AUC = 0.962, sensitivity = 94.74%, specificity = 90.00%, cutoff value = 47.8%) for pathological myopia, whereas the AUC of pRNFL thickness, SRCP, and DRCP were only 0.675, 0.824, and 0.865, respectively. The univariate and multiple linear regression models showed that RPC density, SRCP density, and AL were correlated with BCVA (All p < 0.05). In the final BCVA model with multiple generalized estimating equation analysis, AL, RPC density and interaction between RPC and AL were shown (all p < 0.03). For an eye with AL ≥ 27.94 mm, global RPC density was predicted to be less than 48.77% with a high risk of visual impairment. Conclusion Peripapillary alterations, both the decreasing RPC density and pRNFL thickness, occurred in pathological myopia compared with the control. The RPC density was associated with BCVA, and this relationship was affected by AL.